Protein kinase CK2 links polyamine metabolism to MAPK signalling in Drosophila. - Stark, F.; Pfannstiel, J.; Klaiber, I.; Raabe, T. (Cellular Signalling, 2011)
MAPK signalling is a complex process not only requiring the core components Raf, MEK and Erk, but also many proteins like the scaffold protein KSR and several kinases to specifically localize, modulate and fine-tune the outcome of the pathway in a cell context specific manner. In mammals, protein kinase CK2 was shown to bind to the scaffold protein KSR and to phosphorylate Raf proteins at a conserved serine residue in the negative-charge regulatory (N-) region, thereby facilitating maximal activity of the MAPK signalling pathway. In this work we show that in Drosophila CK2 is also bound to KSR. However, despite the presence of a corresponding serine residue in the N-region of DRaf, CK2-mediated phosphorylation of DRaf takes place on a serine residue at the N-terminus and is required for Erk activation. Previous work identified polyamines as regulators of CK2 kinase activity. The main cellular source of polyamines is the catabolism of amino acids. Evidence is provided that phosphorylation of DRaf by CK2 is modulated by polyamines, with spermine being the most potent inhibitor of the reaction. We suggest that CK2 is able to monitor intracellular polyamine levels and translates this information to modulate MAPK signalling.